دور الحوكمة البيئية في تحقيق التنمية المستدامة - بوعشرين موسى -لوصيف فيصل (جامعة المسيلة, 2024)
In the context of the growing international awareness of the importance of environmental conservation, global environmental governance has emerged and become a global demand, with increasing focus on the mechanisms that facilitate its activation across various parts of the world. The environment has become one of the most significant topics of global concern due to its negative repercussions. Therefore, this study aims to address the issue of the extent to which environmental governance contributes to achieving sustainable development by providing a theoretical framework that defines both terms, and by attempting to understand the importance of environmental governance within the efforts of the United Nations and global environmental protection. Additionally, it highlights the role of global environmental governance actors in achieving sustainable development. The study concludes by emphasizing the necessity of activating the role of environmental governance as a global system and mechanism to achieve sustainable development that ensures the rights of future generations and mitigates the obstacles and challenges that hinder its effectiveness. Key words: environment, governance, environmental governance, sustainable development.
Keywords: البيئة، الحوكمة ، الحوكمة البيئية، التنمية المستدامة.